Impacts of Protecting Life in Global Health Assistance policy in Nepal: a qualitative study - Sarmila Dhakal; Mahesh Puri; Preeti Gautam; Kusum Wagle; Samantha Luffy; Bergen Cooper (BMC, 2023)
Abstract Background Despite the legalization of abortion in 2002 and the concerted efforts of the Ministry of Health and Population, abortion services remain inaccessible for many Nepali women. In 2017, the United States government enacted the Protecting Life in Global Health Assistance (PLGHA) policy, which prohibited international non-governmental organizations (INGOs) from receiving United States global health assistance from providing abortion services or referrals or engaging in advocacy on liberalizing abortion laws that may have had an impact on abortion services. Though this policy was revoked in January 2021, there is a need to assess its impacts in Nepal and mitigate its lingering effects, if any. Methods We conducted in-depth interviews with 21 national-level stakeholders selected purposively on the basis of their experiences and expertise in sexual and reproductive health and rights (SRHR) in Nepal. Interviews were conducted two times: first between August and November 2020 when PLGHA was in place, and then between July and August 2021 after PLGHA was revoked. Interviews were digitally recorded, transcribed, translated and analysed thematically. Results Most participants reported that the implementation of PLGHA created gaps in SRHR services, affecting marginalized and underserved populations in Nepal. Participants reported that this policy has compromised the work of INGOs and civil society organizations (CSOs), posing additional risk to the sustainability of SRHR program achievements made so far. Beyond funding loss, participants also mentioned that PLGHA curtailed their freedom, with limited working areas and partnerships for CSOs leading to low or no utilization of services. Most participants welcomed the revocation of PLGHA and hoped it would have positive impacts on SRHR services by permanently repealing PLGHA. Most participants believed that the revocation of PLGHA opened opportunities for new funding and could re-establish partnerships and collaboration, though immediate results had not yet been seen. Conclusions PLGHA had negative impacts on access to and quality of SRHR services. The Nepal government and other donor agencies need to bridge the funding gap created by the policy. The revocation of the policy has created the hope of bringing positive impacts in SRHR sector; however, the implementation of revocation at the ground level and impacts made on SRHR programs in Nepal remains to be explored.